Brachylaima ezohelicis sp. nov. (Trematoda: Brachylaimidae) found from the land snail Ezohelix gainesi, with a note of an unidentified Brachylaima species in Hokkaido, Japan. Issue 3 (June 2017) - Nakao, Minoru; Waki, Tsukasa; Sasaki, Mizuki; Anders, Jason L.; Koga, Daisuke; Asakawa, Mitsuhiko
Abstract: In the Japanese Archipelago, Ezohelix gainesi, a member of bradybaenid land snails, is endemic mainly to the island of Hokkaido. During July to August of 2016, a survey to detect trematode infections from E. gainesi was carried out at a forest city park in Asahikawa, Hokkaido. Systemic infections of the snails with sporocysts containing short-tailed cercariae were found in 5.3% of 94 individuals examined. Furthermore, most of them (90.4%) harbored non-encysted metacercariae within their kidneys. A DNA sequence identification revealed that both of the sporocyst and the metacercaria belong to an unknown species of the family Brachylaimidae. The metacercariae showed a genetic diversity with 6 haplotypes of mitochondrial DNA (mtDNA) even in the limited sampling area. A definitive host of the unknown species could not be determined, although 34 field mice ( Apodemus speciosus ) and 21 voles ( Myodes rufocanus ) from the city park were examined for intestinal parasites. To examine the adult stage, the metacercariae were perorally administrated to mice, together with anti-inflammatory treatment with methylprednisolone. Fully matured adult worms were recovered from the intestinal ileum 8 and 14 days postinfection. The gravid adults showed typical features of the genus Brachylaima . A morphological and biogeographical evaluation prompted us to propose Brachylaima ezohelicis sp. nov. for the parasite from E. gainesi . The autochthony of the first intermediate host and the spatial heterogeneity of mtDNA suggest that the new species found in the city park is not a recently expanded population of immigrant origin. Graphical abstract: Highlights: Larval brachylaimids were found from Ezohelix gainesi, an indigenous land snail in Hokkaido, Japan. The parasite showed distinct morphologic features and spatial genetic heterogeneity. Brachylaima ezohelicis sp. nov. is proposed for the parasite.